A SiC microdevice for the minimally invasive monitoring of ischemia in living tissues - Gómez, Rodrigo; Ivorra, Antoni; Villa, Rosa; Godignon, Philippe; Millán, José; Erill, Ivan; Solà, Anna; Hotter, Georgina; Palacios, Luís (Springer Nature, 2006)
Monitoring of ischemia in living tissues is a field of increasing interest in many clinical settings. In this work we report for the first time anywhere the development of needle-shaped, minimally-invasive impedance probes based on silicon carbide (SiC) substrates. An in-vitro comparison of these new devices with Si-based impedance probes demonstrates that their effective operation range extends up to the 100 kHz range, thus allowing a wide-spectrum multi-frequency analysis of impedance modulus and phase angle. Furthermore, we show that, when applied to in-vivo settings, this kind of analysis yields to an accurate monitoring of ischemia, while making possible the application of more robust mathematical methods for the study of impedance in living tissues.